Analisis Pembiayaan Bermasalah Pada BMT Assayfi’iyah Kota Gajah - Widodo, Deny Edy; Rahayu, Sri Retnaning; Wahyudi, Galih Ma'ruf (Jurnal Manajemen DIVERSIFIKASI, 2023)
The main factors that are taken into consideration before being given financing are externalfactors or factors caused by customers consisting of character, capacity, capital, collateraland conditions and non-performing financing. This study aims to determine the factors thatcause problematic financing at BMT Assayfi'iyah. The research design is a quantitativedescriptive study using a survey method. The object of research is the character, capacity,capital, guarantee and economic condition of customers with non-performing financing. Thepopulation and research sample are customers with financing problems with the number ofsamples taken as many as 55 customers. Data collection techniques using questionnaires.The analytical tool used is data quality analysis and multiple linear regression analysis withSPSS program. The results showed that character, capacity, capital, collateral and conditionpartially or simultaneously had a positive and significant effect on reducing non-performingfinancing. Based on the coefficient values of all research variables, it can be seen that themost influential factor on non-performing financing is the character factor of the customer